2014
DOI: 10.1136/bmj.g3730
|View full text |Cite
|
Sign up to set email alerts
|

Rapid diagnostic tests to improve treatment of malaria and other febrile illnesses: patient randomised effectiveness trial in primary care clinics in Afghanistan

Abstract: Objective To assess the impact of rapid diagnostic tests on the diagnostic accuracy and treatment of malaria and non-severe fever in an Asian setting.Design Patient randomised trial in primary level clinics.Setting Two areas of Afghanistan where Plasmodium vivax and Plasmodium falciparum are endemic; one area with moderate transmission (eastern region) and one with low transmission (northern region).Participants 5794 patients of all ages with suspected malaria enrolled by 80 clinicians in 22 clinics.Interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 24 publications
2
47
0
Order By: Relevance
“…Detailed descriptions of the individual studies are available in open access publications. [36][37][38][39][40][41][42][43] We included in the analysis studies that met the following criteria: evaluated an intervention to implement rapid diagnostic tests for malaria in settings where participating providers could prescribe both antimalarials and antibiotics, compared sites with and without the intervention, documented prescriber behaviour as a primary outcome, and collected individual patient data on diagnostic test results and treatments prescribed including antibiotics. Tables 1 and 2 present descriptions of the nine studies meeting these criteria.…”
Section: Overview Of Studies Included In Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed descriptions of the individual studies are available in open access publications. [36][37][38][39][40][41][42][43] We included in the analysis studies that met the following criteria: evaluated an intervention to implement rapid diagnostic tests for malaria in settings where participating providers could prescribe both antimalarials and antibiotics, compared sites with and without the intervention, documented prescriber behaviour as a primary outcome, and collected individual patient data on diagnostic test results and treatments prescribed including antibiotics. Tables 1 and 2 present descriptions of the nine studies meeting these criteria.…”
Section: Overview Of Studies Included In Analysismentioning
confidence: 99%
“…Rapid diagnostic tests were introduced among government sponsored community health workers (Afgh-com (T Leslie, et al, in preparation)), in public health facilities only (Afghpub, 36 Cam-pub, 37 Ghan-pub, 38 Tanz1-pub, 40 Tanz2pub, 39 Uga-pub 43 ), in private drug shops only (Uga-priv 41 ), and in a combination of public facilities, private pharmacies, and drug shops (Nige-mix 42 ). Most studies included were cluster randomised trials of interventions, with the exception of two individually randomised trials (Afgh-pub, 36 Ghan-pub 38 ), and one descriptive study before and after national implementation of rapid diagnostic tests (Tanz1-pub 40 ). Table 2 summarises the intervention in each study.…”
Section: Overview Of Studies Included In Analysismentioning
confidence: 99%
“…Again, reasonable number of doctors (20.0%) working in the Internal Medicine department did not perceive mRDT as being useful, while all the doctors working in General Outpatient, and 93.8% of those in Paediatrics departments did not share this wrong perception. mRDT has been shown to be effective even in low transmission areas [25]. Some studies in Africa revealed that using mRDT enhanced correct treatment of malaria more than microscopy [26] [27].…”
Section: Discussionmentioning
confidence: 99%
“…5 The study was carried out in two areas, one in the north of the country where malaria is now rare, and one in the east with a moderate incidence of malaria. In the north only half of the 10 clinics were equipped with microscopy, whereas in the east, microscopy was available in all 12 clinics.…”
mentioning
confidence: 99%
“…5 Patients with suspected malaria based on clinical signs and symptoms were randomised to be managed on the basis of a malaria RDT result or in the usual way (clinically or after microscopy according to local availability). Overall, 1696 patients of all ages were enrolled in the northern region with low transmission (1044 and 652 in clinics with and without microscopy, respectively), and 4053 in the eastern region with moderate transmission (all in clinics with microscopy).…”
mentioning
confidence: 99%